Metaphorical Singular Reference. The Role of Enriched Composition in Reference Resolution - Anne Bezuidenhout (Baltic International Yearbook of Cognition, Logic and Communication, 2007)
It is widely accepted that, in the course of interpreting a metaphorical utterance, both literal and metaphorical interpretations of the utterance are available to the interpreter, although there may be disagreement about the order in which these interpretations are accessed. I call this the dual availability assumption. I argue that it does not apply in cases of metaphorical singular reference. These are cases in which proper names, complex demonstratives or definite descriptions are used metaphorically; e.g., ‘That festering sore must go’, referring to a derelict house. We are forced to give up dual availability in these cases because a process of predicate transfer happens in the restriction clauses of such metaphorically used definite phrases (DPs), so that a denotation-less definite concept is never constructed. A process of enriched composition yields only a metaphorical referent/denotation. I compare cases of metaphorical reference both to cases of metonymic reference and to uses of epithets of the ‘That N of an N’ form. Reflection on the former is helpful in getting clear about the kind of property transfer involved in referential metaphors. Such transfer happens directly at the level of properties and is not mediated via a correspondence between objects, as is the case with metonymic reference. Reflection on epithets such as ‘that festering sore of a house’ is helpful since these are a sort of intermediate case between cases of literal and metaphorical reference. They provide support for my claim that in cases of metaphorical reference there is only a single referent (the metaphorical one). Moreover, constraints on the use of these epithets suggest that referential metaphors are similarly constrained. In particular, I argue that referential metaphors can only be used when the implicit category restriction (e.g., house in the case of the example ‘That festering sore must go’) is highly salient, and that the evaluative information conveyed by the metaphor serves primarily to indicate the speaker’s attitude towards the referent rather than being intended to help the hearer identify the referent.
Keywords: philosophy; linguistics